In laughing memory A correlational study between humor and memory. - Almeria, Christian Dave E., et al.; Serrano, Don Louie P.; Simborio, Vernaliza C. (Tacloban City Christian Dave E. Almeria, Don Louie P. Serrano [and] Vernaliza C. Simborio, 2010)
This study was conducted to determine the influence of exposure to humorous material to memory performance of selected participants. The respondents of this study were composed of 20% randomly selected students from the requested total list of fourth year high school students (ages 15 to 18) of Marasbaras National High School (MNHS) school year 2009-2010. Out of 154, a total of 30 students were selected as final respondents of the study. For an equal distribution of the respondents among the three sections of fourth year students, the researchers have agreed to select 10 respondents using stratified random sampling on each section. They were divided into two equal groups: the Humorous and the Non-humurous group. The humorous group took similar memory tests before and after the exposure to humorous video clip so goes with the non-humorous group. This memory test has two parts: the 20-item visual memory test and the 12-item numerical memory test. Data were analyzed using Pearson Product Moment Correlation. Results showed a significant improvement in memory performances (5%) of both groups after exposing to either humorous or non-humorous video clip. This means that exposure to a video clip regardless of its content could enhance memory performance.
Undergraduate thesis (B.A.S.S. Psychology)--University of the Philippines, Tacloban
Keywords: Social Science